Alfonso Costa Portugal - De Meneses, Filipe Ribeiro, 1969- (Haus histories, 2010)
Portugal's poor military performance in the First World War, notably in Africa, restricted Afonso Costa's (1871-1937) ability to secure his diplomatic aims which, in any case, were highly unrealistic. Nevertheless, his loyal press in Portugal described him as the leader of the small nations', and reported his every statement as a major triumph. Afonso Costa's most important intervention took place in May 1919, when he denounced the Allies' unwillingness to make Germany pay for all the damage she had caused during the conflict; this speech led to a number of newspaper interviews in which Costa restated his position. It is clear that the interventionists needed a favourable Treaty in order to demonstrate to the country that its sacrifices had been worthwhile. The final draft of the Treaty was thus a complete shock to Portuguese public opinion, and came as a major defeat to the interventionists, who saw all their hopes for tangible gain evaporate. It effectively spelt the end of Costa's political career, although this was not yet clear. This biography of Afonso Costa considers the political implications of Portugal's participation in the First World War and of the defeat' in Paris. Reconciliation between the rival parties and between factions within parties became impossible, as did, as a result, the formation of a stable cabinet. With governments following each other in quick succession, it became increasingly difficult to carry out any of the reforms Portugal needed, and the Republic lost much of the support that remained. Nationalist opinion abandoned the regime and turned to the authoritarian models that had been pioneered by Sidonio Pais, and were now spreading throughout Europe. Politically neutral for decades, the army now intervened in politics, overthrowing the government after a failed coup in April 1925 in May 1926. The need for order in politics and on the street was paramount in the minds of the officers who plotted the downfall of the regime. This military dictatorship gave way, in the early 1930s, to Salazar's New State, and the volume concludes with a quick overview of this regime's domestic and foreign policy. Salazar, like Afonso Costa a Coimbra academic, announced Portugal's neutrality when Germany invaded Poland, in 1939, and his wartime diplomacy would be the reverse of Afonso Costa's, some twenty years earlier.